Movement of hidden reserves: empirical evidence from Malaysia / Henny Hazliza Mohd Tahir ... [et al.] - Mohd Tahir, Henny Hazliza; Kadri, Mohd Halim; Haron, Rosmawati; Ibrahim, Muhd Kamil (2012)
Reserves in accounting can be of different kinds and created for diverse reasons. Most of them are revealed publicly in one way or another. When the firm's net worth swerves from its economic value, it is said to have hidden reserves. Two sources of hidden reserves exist: accountant's misevaluation of portfolio positions that accounting principles designates as on balance sheet items and the systematic neglect of off balance sheet sources of value that these principles do not permit to be formally recorded (Kane & Unal, 1990). This paper used the model developed by Kane & Unal (1990) to study the movement of the hidden reserves in Malaysia from the year 1999 to 2008. In effect, the analysis found that the firms' values in Malaysia are overstated and the values of the hidden reserves are insignificant throughout the year under study.